Pengaruh Roa, Car Dan Fdr Terhadap Market Share Bank Syariah Di Indonesia Periode Januari 2015-Mei 2020 - Yuliana, Eva; Fadhilah, Diena; Supaino (Politeknik Negeri Medan, 2021)
This study aims to determine the effect of Return on Assets (ROA), Capital Adequacy Ratio (CAR) and the Effect of Financing to Deposit Ratio (FDR) on the Market share of Islamic Banks in Indonesia for the period January 2015-May 2020. This research is a type of quantitative and technical research. data collection obtained from secondary data. The data analysis technique used in this study is time series data regression analysis using the SPSS 25 computation program. The results of this study indicate that simultaneously the independent variables (ROA, CAR and FDR) have a positive and significant effect on the market share of Islamic banks in Indonesia. Partially, the results show that the variable Return on Assets (ROA) and Financing to Deposit Ratio (FDR) have a negative and significant effect on the market share of Islamic banks in Indonesia. Meanwhile, the Capital Adequacy Ratio (CAR) variable has no significant effect on the market share of Islamic banks in Indonesia. Penelitian ini bertujuan untuk mengetahui pengaruh Return on Assets (ROA), Capital Adequecy Ratio (CAR) dan Pengaruh Financing to Deposit Ratio (FDR) terhadap Market share Bank Syariah di Indonesia periode januari 2015-mei 2020. Penelitian ini merupakan jenis penelitian kuantitatif dan teknik pengumpulan data diperoleh dari data sekunder. Teknik analisis data yang digunakan dalam penelitian ini yaitu analisis regresi data time seriesdengan menggunakan program komputasi SPSS 25. Hasil dari penelitian ini menunjukkan bahwa secara simultan variabel independen (ROA, CAR dan FDR) berpengaruh positif dan signifikan terhadap market share bank syariah di Indonesia. Secara parsial diperoleh hasil bahwa variabel Return on Assets (ROA) dan Financing to DepositRatio (FDR) berpengaruh negatif dan signifikan terhadap market share bank syariah di Indonesia. Sedangkan variabel Capital Adequecy Ratio (CAR) memiliki pengaruh tidak signifikan terhadap market share bank syariah diIndonesia.